Methylation status of VTRNA2-1/nc886 is stable across populations, monozygotic twin pairs and in majority of tissues - Marttila Saara; Tamminen Hely; Rajić Sonja; Mishra Pashupati P; Lehtimäki Terho; Raitakari Olli; Kähönen Mika; Kananen Laura; Jylhävä Juulia; Hägg Sara; Delerue Thomas; Peters Annette; et al. (FUTURE MEDICINE LTD, 2025)
Aims & methods: The aim of this study was to characterize the methylation level of a polymorphically imprinted gene, VTRNA2-1/nc886, in human populations and somatic tissues.48 datasets, consisting of more than 30 tissues and >30,000 individuals, were used.
Results: nc886 methylation status is associated with twin status and ethnic background, but the variation between populations is limited. Monozygotic twin pairs present concordant methylation, whereas similar to 30% of dizygotic twin pairs present discordant methylation in the nc886 locus. The methylation levels of nc886 are uniform across somatic tissues, except in cerebellum and skeletal muscle.
Conclusion: The nc886 imprint may be established in the oocyte, and, after implantation, the methylation status is stable, excluding a few specific tissues.Tweetable abstract Methylation status of a polymorphically imprinted gene, VTRNA2-1/nc886, is stable in human populations (48 cohorts, n > 30,000) and in somatic tissues, except in cerebellum and skeletal muscle. Twin data suggest it may already be established in the oocyte.